Distribución temporal y espacial de la radiación fotosintéticamente activa entre hileras de plátano (Musa AAB) - Jiménez Otárola, Francisco (1997)
The distribution of photosynthetically active radiation (PAR) between plantain rows since planting, at the seasonal level (different dates since planting and every two hours durintg those dates) as well as at the spatial level (different strips between rows) and its relationship with crop growth variables were studied. During the first four months PAR transmitted to the soil was over 90 percent (of the incident on the canopy); however, after eight months it decreased to near 50 percent. Radiation transmitted was closely and conversely associated to leaf area index and other growth variables. Average PAR transmitted was higher for the measurements corresponding to hours 10 and 12.